Pharmacogenomics assists in controlling blood pressure in cardiovascular and cerebrovascular patients during Rehabilitation: a case report - Hou, Tian; Yu, Luhai; Shi, Xiaoliang; Zhen, Yueran; Ji, Longyu; Wei, Zhenbang; Xu, Yipeng (Frontiers in Pharmacology, 2024)
Hypertension is a common risk factor for cardiovascular disease. Pharmacogenomics, as a tool for personalized healthcare, helps in determining the optimal drug treatment based on the genome of individual patient. This study reports a 49-year-old male with acute cerebral infarction, pulmonary infection, extremely high-risk hypertension (grade3), type 2 diabetes, hyperhomocysteinemia, hyperlipidemia, and fatty liver. The patient initially received conventional systemic treatment but continued to have severe hypertension (159/85 mmHg).To better control blood pressure, a pharmacogenomic test was performed, and results showed that the SNP genotype of rs4961 (ADD1) suggests poor efficacy with certain antihypertensive drugs. The genotype of rs4149601 (NEDD4L) indicates better efficacy with hydrochlorothiazide, while the CYP3A5*3 genotype indicates a slow metabolism of calcium channel blockers, suggesting that amlodipine may be more effective than nifedipine.By replacing nifedipine with amlodipine and increasing the dosage of hydrochlorothiazide, the patient's systolic blood pressure was stabilized, although diastolic blood pressure remained suboptimal (131/91 mmHg). Despite low potassium levels, the patient was not sensitive to spironolactone (141/91 mmHg) but achieved exhibited well-controlled blood pressure (129/90 mmHg) with hydrochlorothiazide, consistent with pharmacogenomics recommendations. In summary, pharmacogenomics testing identified genetic variations influencing the patient's response to specific drugs, guiding their selection and administration. This approach can lead to better blood pressure control and reduce the risk of adverse drug events, highlighting the potential of personalized drugs in managing hypertension through pharmacogenomics.